An Improved DTFC based Five Levels - NPC Inverter Fed Induction Motor for Torque Ripple Minimization - P. Rajasekaran; V. Jawahar Senthilkumar (Institute of Advanced Engineering and Science, 2016)
This paper presents a five level Neutral Point Clamped (NPC) inverter fed IM (Induction Motor) drive for variable speed application. In general the stator current is very highly affected by the harmonic components. It can be affecting the torque to produce high torque ripple in IM at maximum to low speed region. Since the drive performances are depends on mathematical model contains the parameters variations, noise, common mode voltage, flux variation and harmonic levels of the machine. Torque ripples and voltage saturations are the most significant problems in drive application. To overcome this problem the DTFC (direct torque and flux control) technique based ﬁve-level neutral-point-clamped (NPC-5L) approach is used. The proposed control scheme uses to stator current error as variable. Through the resistance estimated PI controller rules based the selection of voltage space vector modulation technique is optimized and motor performance level has been improved. The torque & speed are successfully controlled with less torque response. The results are compared and verified with conventional three phases VSI under different control technique by Matlab/Simulink.